2017
DOI: 10.1371/journal.pone.0180634
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk associated with high sodium-containing drugs: A systematic review

Abstract: BackgroundExcess dietary sodium is associated with increased blood pressure (BP). Some drugs are associated with high sodium intake (in particular effervescent tablets), but the cardiovascular risk associated with such high sodium-containing drugs (HSCD) is largely underevaluated.ObjectivesTo summarize the evidence for a potential cardiovascular risk associated with exposure to HSCD, and to highlight possible risk factors associated with this iatrogenic issue; in general and/or specific populations.MethodsWe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…We were not able to explore the factors other than age and sex, which might be associated with medication prescription or discontinuation as suggested by other previous publications. 9 10 Furthermore, we were not able to include all dispersible, effervescent or soluble formulations available on prescription. As we aimed to investigate the impact of the publication, we included all equivalent formulations to the drugs included in the original publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were not able to explore the factors other than age and sex, which might be associated with medication prescription or discontinuation as suggested by other previous publications. 9 10 Furthermore, we were not able to include all dispersible, effervescent or soluble formulations available on prescription. As we aimed to investigate the impact of the publication, we included all equivalent formulations to the drugs included in the original publication.…”
Section: Discussionmentioning
confidence: 99%
“…The results were later confirmed by a randomised, crossover trial evaluating the effect of effervescent paracetamol on blood pressure 8 and a meta-analysis of eight studies. 9 In 2015, the Pharmacovigilance Risk Assessment Committee of the European Medicines Agency (EMA) adopted the findings and have suggested labelling changes to these high sodium-containing medications. With regard to the use of sodium-containing medications, to date, there is only one recent French study that evaluated factors associated with exposure to effervescent drugs, 10 while there is no updated information on prescribing patterns of sodium-containing medicines following the BMJ publication and EMA guideline changes.…”
Section: Introductionmentioning
confidence: 99%
“…The main source of sodium intake is bread, cheese and processed food, which are estimated to contribute up to 75% of daily salt intake [14,15]. Another 20% percent are considered be salt added by the consumer, which leaves 5% coming from water and medicines [14].…”
Section: Discussionmentioning
confidence: 99%
“…and 2 powder formulations (P1, P2 in Table 3.). Perrin et al (2018) have concluded that daily sodium intake through consumption of high-sodium containing medicines (such as effervescents) higher than 1500 mg, long-term exposure to these medicines, as well as presence of comorbidities (especially hypertension and diabetes mellitus) increase the risk of cardiovascular complications [15]. By this criteria, effervescent granules (Table 2.) and powders ( Table 3.)…”
Section: Discussionmentioning
confidence: 99%
“…These high-sodium containing drugs (HSCDs) could theoretically provoke or worsen cardiovascular conditions, especially hypertension, if taken on a regular basis and/or at a high dose. 11 ETs are generally not indicated for patients who require low-salt or normal salt diets (patients with hypertension and those with congestive heart failure), as non-effervescent alternatives are available. 12 A population-based nested case–control study, published by George et al 13 in 2013, showed that patients diagnosed with hypertension or cardiovascular events (non-fatal myocardial infarction, non-fatal stroke or those who died from a vascular cause) were more likely to be prescribed HSCDs.…”
Section: Introductionmentioning
confidence: 99%